PERANAN SIMBOL BENDA-BENDA LANGIT DALAM PERKEMBANGAN RELIGI MASYARAKAT DI INDONESIA - Hartatik (Berkala Arkeologi, 1999)
Celestial objects are always present in the form of symbols depicted in rock paintings, nekara, megalithic concepts, symbols of royal triumph and in conventional myths as can be found in the ethnographic data of several tribes in Indonesia. In general, celestial bodies, especially the sun, moon and stars are symbols whose rays are considered to be the source of life, the light of truth and justice that are expected to be able to illuminate mankind. In their development, the role of celestial bodies has shifted from a religious function to a global function that tends to be profane, which includes social and political functions. However, the presence of a symbol representing an infinite character always exists as a generator of feelings of togetherness and a deeper attachment than just a verbal formulation.